Extended durotomy to treat severe spinal cord injury after acute thoracolumbar disc herniation in dogs. Issue 5 (11th April 2020) - Jeffery, Nick D.; Mankin, Joe M.; Ito, Daisuke; Boudreau, C. Elizabeth; Kerwin, Sharon C.; Levine, Jon M.; Krasnow, Maya S.; Andruzzi, Melissa N.; Alcott, Cody J.; Granger, Nicolas
Abstract: Objective: To report recovery of ambulation of dogs treated with extended thoracolumbar durotomy for severe spinal cord injury caused by intervertebral disc herniation. Study design: Descriptive cohort. Animals: Twenty‐six consecutive paraplegic dogs presented with loss of deep pain sensation after acute thoracolumbar intervertebral disc herniation. Methods: Each dog underwent routine diagnostic assessment and surgery for removal of extradural herniated intervertebral disc, followed by a four‐vertebral body length durotomy centered on the herniated disc. Each dog was followed up until it was able to walk 10 steps without assistance or until 6 months after surgery. Results: Sixteen of 26 dogs recovered to walk unaided (all but one also recovered fecal and urinary continence), and six dogs did not; four dogs were lost to follow‐up. One dog was euthanized because of signs consistent with progressive myelomalacia. There was no evidence of detrimental effects of durotomy within the period of study. Using Bayesian analysis, we found a point estimate of successful outcome of 71% with 95% credible interval from 52% to 87%. Conclusion: Extended durotomy seemed to improve the outcome of dogs in our case series without increase in morbidity. Clinical significance: Extended durotomy appears safe and may improve the outcome of dogs with severe thoracolumbar mixed contusion and compressive injuries associated with acute intervertebral disc extrusion.